Sport at the World Festival of Youth and Students: Between Olympic Ideals and Socialist Internationalism - Lesnykh, Lidia (Frontiers in Sports and Active Living, 2020)
During the first decade of the Cold War, the communist-sponsored World Festivals of Youth and Students included a program of international sports events that provided elite athletes with a self-standing arena of international competition. They also encouraged mass participation in sports, without social, racial, or political discrimination, thereby implicitly questioning elitism in sport. The present paper argues that through the World Festivals of Youth and Students, the Soviet Union harnessed the universal language of sport as a tool of cultural diplomacy with which to expand develop an international socialist sports youth network. The Festival sporting events represented an alternative model of international sport, run in parallel to the Olympics, whose ideals of peace, friendship, and mutual understanding they shared.